Integration of Customer Data Management in a Web-Based Fishing Profile Application - Susila, Mochamad Nandi; Fridayanthie, Eka Wulansari; Haryanto, H. (Golden Ratio of Data in Summary, 2025)
The advancement of communication media and technology has driven various business sectors to transform digitally, including fishing businesses in South Tangerang City. However, many fishing businesses still lack adequate information systems to manage company profiles and customer data in an integrated manner. This research aims to analyze, design, and implement a fishing profile website equipped with customer data management features using the Waterfall software development methodology. The waterfall methodology was chosen for its systematic and structured approach, which involves five main stages: requirements analysis, system design, implementation, testing, and maintenance. The process begins with requirements analysis and collecting necessary customer data to proceed to the data integration stage, followed by system design and implementation by developing a user-friendly web-based fishing profile application. System testing uses black box testing to ensure all features function properly. The research results show that the developed fishing profile website provides professional information and manages customer data, including customer registration, visit history, and service preferences for available fishing products. This system can enhance operational efficiency and strengthen fishing businesses' customer relationships. In conclusion, integrating customer data into a fishing business profile website can serve as an effective solution to support digital transformation in this sector.